(untitled) (The Voz a Vos Bulletin, 2023)
This article can be read as a swarm of conclusions, reflections, experiences or political decisions that emerge from the current research developed from the Research/Creation modality and are installed in the dialogue of Art, Ethics and Politics of Master in Art, Education and Culture at National Pedagogical University. Relationships are established between the situated performative practices of the teacher-creator “I” and the urban public spaces, evidencing the life of the bees as a symbolic universe due to their ways of inhabiting and building their hive, the way they communicate, the work uninterrupted throughout its life and the “bee space” understood in this research as a place of transit in the hive, a Liminal space.